Korban Penyalahguna dan Pemakai Narkotika dalam Undang-Undang No. 35 Tahun 2009 tentang Narkotika - AZWAR AZWAR (Himpunan Ilmu Hukum dan Ilmu Hukum Islam, 2026)
The Constitutional rights of citizens are the rights regulated in the 1945 Constitution which includes the right to life, the right to have a family and continue the lineage, the right to develop oneself, the right to obtain justice, the right to personal freedom, the right to a sense of security, the right to welfare and the Indonesian government is obliged to guarantee and protect the rights of its citizens. Therefore, for Drug Users, Addicts and Victims of Drug Abuse, their constitutional rights must still be given, part of the form of guarantee of fundamental rights guaranteed by the constitution. As a state of law, Indonesia is obliged to guarantee and protect the rights of its citizens, as referred to in Article 28A and Article 28 H of the 1945 Constitution. The elaboration of constitutional rights for Drug Users, Addicts and Victims of Drug Abuse is outlined hierarchically through Law No. 35 of 2009, concerning Narcotics. In the Narcotics Law, where Article 54 and Article 103 focus more on rehabilitation, while Article 127 provides criminal penalties, but also opens up opportunities for rehabilitation for victims, so that the handling is comprehensive. Drug abusers need to undergo rehabilitation as a form of recovery aligned with criminal liability. From a legal and normative perspective, drug addicts are essentially victims suffering from a disease and require physical and psychological treatment, as well as community support, to return to a normal life. Imprisonment alone is insufficient, consistent with the perspective of Law Number 35 of 2009 concerning Narcotics.